El estancamiento de la actividad emprendedora en la informalidad y sus factores de decisión. - Armijos Arias, Jilson Alexander; Santiago Bartolo, Paul Francisco (My University, 2021)
Entrepreneurship in Ecuador is considered a fundamental activity for its development; because it generates employment, distributes wealth and dynamizes the economy. However, despite the progressive growth of entrepreneurship, there are still barriers that hinder its insertion within a legal framework, making it one of the countries with the highest rates of informal entrepreneurial activity in the region. In this sense, the purpose of this paper is to determine the factors associated with the decision to formalize informal enterprises. To this end, the research was developed with a non-experimental transactional design, with descriptive and correlational scope for the analysis of the most relevant characteristics and the evaluation of the relationship of dependence between variables; a simple random sample of three hundred and one informal entrepreneurs located in the central area of the city of Machala was also used. The results show that there is a high percentage of middle-aged and older adults who have been running their businesses for decades in the informal sector, mainly motivated by the need to; most of them have completed secondary school or high school, their salaries are below the basic salary and they do not perceive the desired flexibility or economic independence. Therefore, it is concluded that, although entrepreneurs have the experience and ability to trade, the decision to formalize and stagnate in informality are associated with low- and middle-income levels, as well as the absence of external financing.
El emprendimiento en Ecuador es considerado como una actividad fundamental para su desarrollo; porque genera empleo, distribuye la riqueza y dinamiza la economía. Sin embargo, pese al crecimiento progresivo emprendedor, aún existen barreras que frenan su inserción dentro de un marco legal, convirtiéndolo en uno de los países con los más altos índices de actividad emprendedora informal de la región. En ese sentido el presente trabajo tiene como objetivo determinar los factores que se asocian a la decisión de formalizar los emprendimientos situados en la informalidad. A fin de ello, se desarrolló la investigación con un diseño transaccional no experimental, con alcance descriptivo y correlacional, para el análisis de las características más relevantes y la evaluación de relación de dependencia entre variables; también se utilizó una muestra aleatoria simple de trescientos y uno emprendedores informales ubicados en el casco central de la ciudad de Machala. Los resultados dan cuenta que, existe un alto porcentaje de adultos de mediana edad y adultos mayores que llevan con sus emprendimientos por décadas en la informalidad, motivados principalmente por la necesidad; la mayoría tienen estudios secundarios o bachilleratos culminados, remuneraciones por debajo del salario básico y no se percibe la flexibilidad ni la independencia económica deseada. Por lo tanto, aunque los emprendedores cuenten con la experiencia y habilidad para el comercio; la decisión de formalizarse y estancarse en la informalidad, están asociados a niveles de ingresos bajos y medios, así como a la ausencia del financiamiento externo.
Keywords: EMPRENDIMIENTO; INFORMALIDAD; DECISIÓN; ESTANCAMIENTO